Frameworks for central-local government relations and fiscal sustainability - Peter J. Morgan; Long Q. Trinh (Asian Development Bank Institute (ADBI), 2016)
Sustainable and inclusive growth in emerging Asian economies requires continued high levels of public sector investment in areas such as infrastructure, education, health, and social services. These responsibilities, especially with regard to infrastructure investment, need to be devolved increasingly to the regional government level. However, growth of sources of revenue and financing for local governments has not necessarily kept pace, forcing them, in some cases, to increase borrowing or cut spending below needed levels. This paper reviews alternative models of the relationship between central and local governments, and provides an overview and assessment of different financing mechanisms for local governments, including tax revenues, central government transfers, bank loans, and bond issuance, with a focus on the context of emerging Asian economies. The paper also reviews financing mechanisms for local governments and mechanisms for maintaining fiscal stability and sustainability at both the central and local government levels. Based upon the evidence on the decentralization process in Asia, it proposes some policy implications for improving central-local government relations and fiscal sustainability.
Keywords: H70; H71; H72; H74; H77; 330; Government decentralization; government fiscal balance; intra-government transfers; expenditure assignment; revenue assignment; local government borrowing; mechanisms for fiscal stability